Land Certification, Adjustment Experience, and Green Production Technology Acceptance of Farmers: Evidence from Sichuan Province, China - Xinyue Qu; Wenfeng Zhou; Jia He; Dingde Xu (Land, 2023)
Land certification and adjustment experience, which are of great significance to strengthen farmers’ acceptance of the green production technologies (the GPTs), are important factors that affect the stability of land property. Based on the research data of 540 farmers in Sichuan, China, the probit model is used in this research to explore the effect of the land certification upon the GPTs acceptance of farmers and discuss the moderation effect of land adjustment experience (large-scale adjustment and small-scale adjustment). The results show the following. (1) Overall, 10% of the farmers have not obtained the certificates, 17% of the farmers have experienced small-scale land adjustment, and 3% of the farmers have experienced large-scale land adjustment. Meanwhile, 15% of the farmers have not adopted any the green production technologies (the GPTs), and the rest have adopted at least one green production technology. (2) Land certification affects farmers’ acceptance of the GPTs in a significant way. (3) Small-scale land adjustment will weaken the role of land certification in promoting farmers’ acceptance of the green production technologies (the GPTs), while large-scale land adjustment will not. (4) For farmers with large scale of land, low extent of land fragmentation, and high extent of dependence on agricultural income, land certification will positively promote farmers’ decision making on whether to accept the GPTs.